Juridical Review of Banking Law on Business Law Violations: The Case of Micro, Small, and Medium Enterprises (MSMEs) Operated by Foreign Nationals Exploiting OSS Licensing Loopholes in Bali (2020-2024) - Komang Putri Wira Ivana (International Journal of Sociology and Law, 2026)
This study addresses the troubling increase in illegally managed micro, small, and medium enterprises (UMKM) operated by foreign nationals in Bali, which poses significant threats to local economic stability and fairness. The analysis focuses on the legal frameworks governing UMKM, including Law No. 20 of 2008 and the Online Single Submission (OSS) system, as well as the regulatory gaps that allow foreign entities to exploit these mechanisms for their gain. A multi-method approach was employed to evaluate the current situation, emphasizing the roles of local government initiatives, banking regulations, and community engagement in combating illegal business operations. The findings reveal a pressing need for enhanced verification processes, stricter compliance measures, and localized regulations to protect legitimate businesses from exploitation by foreign competitors. The study concludes that only through coordinated efforts among government bodies, financial institutions, and local enterprises can Bali achieve sustainable economic growth, ensuring that UMKM can thrive within a fair and equitable commercial landscape.